Decolorization of Direct Red 81 in Aqueous Solutions by Fenton Oxidation Process: Effect of System Parameters - Mansooreh Dehghani; Yasamin Zonnon; Elham Nourozi; Narges Shamsedini (Iranian Journal of Health, Safety and Environment, 2019)
Dye industries and textile are among the most water-consuming industries, which severely disturb the aquatic life. Therefore, the aim of this study was to determine the feasibility of Fenton process in removing Direct Red 81 dye from aqueous solutions and the optimal conditions for maximum removal. This research was conducted in a laboratory-scale using a one-litre photochemical reactor. The effect of the influential parameters, including pH (3-9), Fe (II) concentration (10-150mg/L), H2O2 concentration (20-150mg/L), initial dye concentration (25-150mg/L), and reaction time (15-120min) on the dye removal was investigated and the optimal conditions were determined according to maximum dye removal efficiency The results showed that the dye removal rate increased as the pH and Fe(II) concentration decreased and as the initial dye concentration and time increased. The optimal condition was at pH=3, Fe (II)=10mg/L, H2O2=50mg/L, initial dye concentration=100mg/L, and reaction time= 45 minutes. Although the maximum removal efficiency (98.29%) was obtained at the reaction time of 120 minutes, 45 min was the appropriate reaction time considering the cost-effectiveness. Our results suggest that the Fenton process is a reliable and efficient method with more than 95% efficiency for decolourization of DR-81 dye and many industrial wastewaters.